Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) April 19-21, 2016, Tomsk, Russia [proceedings] - Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Bulba E. E. Elena Evgenievna; Zhdanova A. O. Alena Olegovna (Les Ulis, 2016)
Title screen